2014
DOI: 10.1111/anae.12932
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Patent Blue dye on peripheral and cerebral oxyhaemoglobin saturations

Abstract: SummaryWe measured the effect of Patent Blue dye on oxyhaemoglobin saturations after injection into breast tissue: 40 women had anaesthesia for breast surgery maintained with sevoflurane or propofol (20 randomly allocated to each). Saturations were recorded with a digital pulse oximeter, in arterial blood samples and with a cerebral tissue oximeter before dye injection and 10, 20, 30, 40, 50, 60, 75, 90, 105 and 120 min afterwards. Patent Blue did not decrease arterial blood oxyhaemoglobin saturation, but it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Latency of desaturation observed in our patient, is due to the site of injection of patent blue (subcutaneous). Intravascular injection causes an immediate drop in oxygen saturation [9]. Anesthesiologist should be aware of this dye and its interference with pulse oximetry, and our case report proves that point.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Latency of desaturation observed in our patient, is due to the site of injection of patent blue (subcutaneous). Intravascular injection causes an immediate drop in oxygen saturation [9]. Anesthesiologist should be aware of this dye and its interference with pulse oximetry, and our case report proves that point.…”
Section: Discussionsupporting
confidence: 66%
“…One of the most common drawbacks seen with the use of patent blue is interference with wavelength reading used to measure the oxyhemoglobin. It leads to factitious transient desaturation in digital pulse oximeter, without changes in arterial blood gas analysis values [9]. Latency of desaturation observed in our patient, is due to the site of injection of patent blue (subcutaneous).…”
Section: Discussionmentioning
confidence: 53%
“…43 As Patent Blue dye interferes with pulse oximetry (causing spuriously low readings), there is a potential delay in the recognition of onset of anaphylaxis. While two studies examining this effect reported mean reductions in digital oxygen saturation (SpO 2 ) of <2%, 11,45 in some individuals, considerably greater falls can be observed. 46,47 In NAP6, reactions to Patent Blue dye were relatively common, were severe, and required significant resuscitation.…”
Section: Patent Blue Dyementioning
confidence: 99%
“…Studies have been published on the effects of patent blue dye on pulse oximetry readings [4][5][6][7][8][9] though there have been no reports on its use in patients with congenital methemoglobinemia. This case illustrates how patent blue dye can be a confounder for poor saturation readings in these patients and may also falsely depress readings for a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%
“…It binds to albumin and is excreted in both the urine and bile [5]. The extent and duration of interference with peripheral pulse oximetry is largely determined by its dose and excretion rate from the systemic circulation [6]. Mammary parenchymal injection of patent blue dye has been found to decrease SpO 2 readings by up to 11% (average 5%) after 15 to 30 minutes [7].…”
Section: Descriptionmentioning
confidence: 99%